MO811: A Closed Loop Audit of CKD-MBD Parameters in Patients Receiving Home Haemodialysis in North West London Centre. (3rd May 2022) - Shahid, Kainat; Sahota, Shaan; Dilloway, Tina; Dassanayake, Thushara; Coloma, Normandy; Capitan, Adrian; Boller, Nicole; Punzalan, Sally; Duncan, Neill
Abstract: BACKGROUND AND AIMS: Hyperphosphatemia is common in end-stage renal disease and increases the risk of fractures, cardiovascular disease and all-cause mortality. Achieving normal phosphate levels is dependent on optimization of dialysis, diet and phosphate medication. Home haemodialysis (HHD) offers exciting opportunities for individualised approaches to management, allowing for a more liberal, lifestyle-centred patient experience. Our aim was to determine, in line with the UK Renal Association 2015 standards for Chronic Kidney Disease—Mineral Bone Disease (CKD-MBD), the percentage of patients in the North West London HHD program with: All bone parameters within target range [calcium 2.2–2.5 mmol/L/phosphate 1.1–1.7 mmol/L/parathyroid hormone (PTH) 2–9× the upper limit of normal (ULN)]. And specifically, serum phosphate between 1.1 and 1.7 mmol/L. METHOD: We conducted a retrospective review of the six most recent monthly biochemistry results for serum phosphate, corrected calcium and PTH levels of all patients actively receiving HHD under the care of Hammersmith Hospital ( n  = 33) between January and September 2020. Subsequently, a monthly multidisciplinary review of blood tests (with nephrologists, specialist nurses and dieticians) focusing on CKD-MBD parameters was implemented to facilitate timely prescription changes. Additionally, two questionnaires were conducted: (1) an adapted Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS) questionnaire assessed adherence with phosphate binders and (2) a diet questionnaire assessed dietary phosphate knowledge. At the end of 12 months, a re-audit was conducted in the patients from the original cohort ( n  = 23; following 4 transplants, 3 in-centre transitions and 3 deaths). RESULTS: The initial audit revealed that of the 33 included patients, 14 (42%) recorded all bone parameters within the target range. Examining CKD-MBD parameters individually, 27 (82%) had adjusted calcium within target range [4 (12%) < 2.2 mmol/L and 1 (3%) > 2.6 mmol/L], 22 (66%) had a serum PTH in target range [9 (27%) > 9× ULN and 2 (8%) < 2× ULN, excluding those with parathyroidectomies] and 17 (51%) recorded a median serum phosphate within target [11 (33%) > 1.7 mmol/L and 5 (15%) <1.1 mmol/L]. Table 1 summarizes baseline demographics of the final audit group ( n  = 23). Re-audit after 12 months revealed 10 (43%) recorded all bone parameters within the target range. Examining CKD-MBD parameters individually, PTH targets had improved (from 66% to 83%). This was associated with increased use of calcimimetics, with 3 (17%) recording PTH > 9× ULN [from 9 (27%) at baseline]. However, there was no significant change in phosphate [12 (54%) within the target range, 7 (29%) above the range] and calcium [18 (78%) within the target range]. Of the 23 patients included for final analysis, 15 (65%) were actively prescribed phosphate binders. The BAASIS questionnaire revealed notable non-adherence, with 8 (53%) admitting to having missed doses in the last month, 5 (33%) consistently missing >4 doses and 6 (40%) not consuming alongside meals. Additionally, the dietary questionnaire revealed a lack of knowledge of hidden sources of dietary phosphate in all surveyed patients ( n  = 11 responses). CONCLUSION: Based on UK Renal Association 2015 standards for CKD-MBD, in patients undergoing HHD: Over half are failing to maintain all serum bone parameters within target range. Approximately one-third have hyperphosphataemia. Despite high prescription of phosphate binders (65%), compliance and understanding of dietary phosphate sources is suboptimal and likely contributory to sub-standard CKD-MBD targets. Therapeutic measures should support patient self-management strategies through facilitating medication compliance and dietary awareness. Increased dialysis time to enhance phosphate clearance remains an option based on individual patient preference.